2017
DOI: 10.21037/jovs.2017.10.03
|View full text |Cite
|
Sign up to set email alerts
|

Subxiphoid single incision thoracoscopic surgery approach for thymectomy: a case report

Abstract: Thoracic surgery is rapidly evolving with minimally invasive strategies now dominating.Thymectomy has traditionally been performed through a sternotomy, but more recently video-assisted thoracoscopic surgery (VATS) approaches have become increasingly popular. To further minimise surgical impact, the uniportal subxiphoid VATS technique has recently been described, using a muscle sparing incision that avoids intercostal nerve injury. A potential advantage that makes this approach particularly suited to thymectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Several studies have found that by using the subxiphoid approach during surgery, the thymoma tissue, diagnosed as Masaoka III, invades the pericardium, lung tissue, and the left innominate vein can also completely be removed and reduce postoperative pain. [36][37][38][39][40] In our subgroup analysis, the results showed that for surgery with the unilateral thoracic approach, the RATS group was still associated with lower blood loss, shorter length of postoperative hospital stay and postoperative duration of drainage, and fewer postoperative complications. For the subxiphoid approach, the RATS group had a shorter duration of postoperative drainage time, lower volume of drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found that by using the subxiphoid approach during surgery, the thymoma tissue, diagnosed as Masaoka III, invades the pericardium, lung tissue, and the left innominate vein can also completely be removed and reduce postoperative pain. [36][37][38][39][40] In our subgroup analysis, the results showed that for surgery with the unilateral thoracic approach, the RATS group was still associated with lower blood loss, shorter length of postoperative hospital stay and postoperative duration of drainage, and fewer postoperative complications. For the subxiphoid approach, the RATS group had a shorter duration of postoperative drainage time, lower volume of drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that by using the subxiphoid approach during surgery, the thymoma tissue, diagnosed as Masaoka III, invades the pericardium, lung tissue, and the left innominate vein can also completely be removed and reduce postoperative pain. 36 , 37 , 38 , 39 , 40…”
Section: Discussionmentioning
confidence: 99%
“…To date there are only isolated case reports describing the uniportal subxiphoid-VATS technique for thymectomy (12,13). This case series adds further to the evidence that the subxiphoid-VATS uniportal approach is a safe and appropriate method for thymic resection in a selected patient group, i.e., non-obese patients with Masaoka stage 1 tumours and without significant underlying cardiorespiratory disease.…”
Section: Discussionmentioning
confidence: 60%
“…In the case of standard VATS, there are reports of requiring rib spreading and the lung being retrieved in pieces. Furthermore, retrieval may result in compression of the intercostal nerves which can result in chest wall pain which may be chronic in some patients More recently, the subxiphoid uniportal VATS technique has been described, avoiding any intercostal incision or instrumentation (14)(15)(16)(17)(18)(19)(20)(21)28,29). Additionally, since the chest drains are not entering the thoracic cavity through intercostal spaces postoperatively, they do not impinge on the intercostal neurovascular bundle during mobilization of the patient.…”
Section: Discussionmentioning
confidence: 99%